Expanding choice through online contraception: a theory of change to inform service development and evaluation. Issue 2 (1st November 2019) - Rezel-Potts, Emma; Free, Caroline; Syred, Jonathan; Baraitser, Paula
Abstract : Background: This study presents the theory of change underpinning an intervention to provide online contraceptive care in an inner London area with high rates of unplanned pregnancy. It aims to suggest attributes of an effective service and to identify key questions for its evaluation. Methods: Thematic analysis of an online sexual and reproductive health programme funding application and 21 semi-structured interviews with a purposive sample of stakeholders selected to provide expertise in contraception and online health. Results: A theory of change model summarised the positive processes of change which could be initiated through increased access to contraceptive supplies, online information and remote interaction and support. Stakeholders predicted that perceptions of convenience and anonymity of online access would vary across the target population. They stressed the importance of trusting service-users' capabilities for autonomous contraceptive decision-making, but expressed concerns that online access could be detrimental for those requiring more complex care. Concerns were alleviated by the prospect of responsive support through text messaging and phone calls, and when the online service was positioned as part of a broader system of provision including physical services. Conclusions: This study has revealed priority areas for the ongoing development of an online contraception service and pertinent evaluation questions. Evaluative research should test assumptions within the theory of change model, exploring the characteristics and circumstances of those preferring online access over existing services and the value of convenience, anonymity, autonomous access and responsive support in executing effective contraceptive choices within a new landscape of contraceptive delivery.